PENGARUH PROMOSI, KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN PADA ROKOK GUDANG GARAM DI SURAKARTA - Della Sitta Kartika Sari (STIE AUB Surakarta, 2018)
This study aims to provide empirical evidence that promotion, product quality and brand image have a positive effect on consumer satisfaction on cigarettes in salt warehouses in Surakarta. The data used in this study is primary data. Samples taken for study are 100 consumers from the existing population. The analytical method used is Data Quality Test, Classical Assumption Test, Multiple Linear Regression Analysis With Test of Determination Coefficient (R2), F Test, and t Test. The results of this study indicate that both partially and simultaneously promotion, product quality and brand image have a significant effect on consumer satisfaction on salt warehouse cigarettes in Surakarta. Based on the results of calculations for multiple linear regression Y = 5.763 + 0.164X1 + 0.977X2 + 0.743X3, calculation results for the f test of 179,516 the value of adjusted R2 is obtained by the coefficient of determination or adjusted R2 of 0.844, meaning that 84.4% of the variables of consumer satisfaction on cigarettes of salt warehouses in Surakarta. can be explained by variations in promotion variables, product quality and brand image, while the remaining 15.6% is influenced by other variables not examined. Whereas the biggest effect is the product quality variable.Keywords: Promotion, Product Quality, Brand Image, Consumer Satisfaction